SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TEAM LEADER PROGRAM KEWIRAUSAHAAN MAHASISWA DENGAN METODE ARAS - Jati, Dewi Sekar; Bangun, Budianto; Sihombing, Volvo (Politeknik Bisnis Indonesia, 2024)
This study aims to design and implement a Decision Support System (DSS) using the Additive Ratio Assessment (ARAS) method in selecting Team Leaders in the Student Entrepreneurship Program at Labuhanbatu University (ULB). The ARAS method was chosen because of its ability to handle multi-criteria decisions by considering various factors, such as leadership, communication, creativity, decision making, and target achievement time. This study involves the stages of determining criteria and weights for each criterion, data collection, and implementing the ARAS method to obtain candidate rankings based on predetermined criteria. Based on data processing, the top three alternatives are MLK_08 with the highest score, followed by MLK_06 and MLK_05. The results of the study indicate that by using this system, the Team Leader selection process can be carried out more objectively and efficiently, thus helping supervisors and entrepreneurship program managers at ULB in determining the best team leader. This system makes an important contribution to improving the selection process and increasing the quality of implementation of the student entrepreneurship program.